Speech therapeutic strategies for rehabilitation of neurogenic dysphagia in adult patients (Research, Society and Development, 2025)
Introduction: neurogenic dysphagia poses a significant challenge for healthcare professionals, particularly speech-language pathologists, due to its complexity and impact on individuals' quality of life. Therapeutic strategies play a fundamental role in the rehabilitation of these patients, aiming to improve the safety of swallowing, the effectiveness of deglutition, as well as social reintegration and nutritional intake. This study aims to report the main approaches and techniques used in clinical practice for the treatment of neurogenic dysphagia in adults, highlighting scientific evidence and future perspectives through an integrative literature review. Methodology: this integrative literature review was guided by the question: what speech-language therapeutic strategies are used in the rehabilitation of neurogenic dysphagia in adult patients? Databases used included the virtual health library, capes journal portal, and scielo, following inclusion and exclusion criteria for portuguese-language articles published between 2019 and 2023. Results and discussion: the analysis of the nine articles included revealed the need for an individualized and multidisciplinary approach to treating neurogenic dysphagia, considering the patient's unique clinical characteristics and complexity. However, gaps remain in the literature regarding reports on different techniques and the optimal duration of treatments. Conclusion: the study reported that the most common speech-language rehabilitation strategies included myofunctional exercises, adaptation of food consistencies, vocal exercises, the chin-tuck protective maneuver, and the mendelsohn maneuver. Despite advances, the findings highlight the ongoing need for new studies and innovations to improve care delivery.